Design of strategies for an efficient and applicative transition from the linear economy to the circular economy, Colombia case (2022)
The process of transition from linear economy to the circular economy has shown progress in other countries thanks to the strategies implemented, by analyzing these from the perspective of some authors, it was possible to identify which ones can be replicated in the country. The approach of this article is qualitative of a proactive documentary type with an inductive method, the sources were secondary, from databases such as Dialnet, Scielo, Academic Google, repository of universities, books, foundation reports and DANE reports, also information was obtained from a primary source through a dialogue whit recyclers and owners of warehouses in the village of La Playa and Barranquilla. Through the sources, essential strategies for sustainable development in Colombia were analyzed, such as: pedagogical strategies focused on changing the behavior of the various sectors of the community through educational campaigns, technological innovation strategies that allow the development of consumer goods that generate the least environmental impact, and social strategies. It was concluded that eco-design, the implementation of innovative technology and access to loans for circular activities are essential for the development of the model, in addition, successful experiences of developed countries in term of C.E can be replicated since they offer the opportunity to improved through pedagogical technological and social strategies.